C Identification of the major genetic contributors to tetralogy of fallot. (May 2019) - Page, Donna J; Miossec, Matthieu J; Williams, Simon G; Monaghan, Richard M; Fotiou, Elisavet; Cordell, Heather J; Sutcliffe, Louise; Topf, Ana; Bourgey, Mathieu; Bourque, Guillaume; Eveleigh, Robert; Dunwoodie, Sally L; et al.
Abstract : There is strong evidence from familial recurrence studies for a genetic predisposition to sporadic, non-syndromic Tetralogy of Fallot (TOF). TOF is the most common, cyanotic congenital heart disease (CHD) phenotype yet the cause for the majority of cases remains elusive. Rare genetic variants have been identified as important contributors to the risk of CHD, but relatively small numbers of TOF cases have been studied to date. 829 TOF patients underwent whole exome sequencing (WES), the largest cohort of non-syndromic TOF patients reported to date. The prevalence of unique, deleterious variants was determined; defined by their absence in the Genome Aggregation Database (gnomAD) and a scaled combined annotation-dependent depletion (CADD) score of ≥20. Clustering analysis of variants revealed that two genes, NOTCH1 and FLT4, surpassed thresholds for genome-wide significance (assigned as P<5 × 10 -8 ), after correction for multiple comparisons. NOTCH1 was most frequently found to harbour unique, deleterious variants. 31 variants were observed in 37 probands (4.5%; 95% confidence interval [CI]: 3.2–6.1%) and included seven loss-of-function variants, 22 missense variants and two in-frame indels. Sanger sequencing of the unaffected parents of seven cases identified five de novo variants. Three NOTCH1 variants (p.G200R, p.C607Y and p.N1875S) were subjected to functional evaluation and two showed a reduction in Jagged1-induced NOTCH signalling. FLT4 variants were found in 2.4% (95% CI:1.6–3.8%) of TOF patients, with 21 patients harbouring 22 unique, deleterious variants. The variants identified were distinct to those that cause the congenital lymphoedema syndrome Milroy disease. In addition to NOTCH1, FLT4 and the well-established TOF gene, TBX1, we identified potential association with variants in several other biologically plausible candidate genes. In summary, the NOTCH1 locus is the most frequent site of genetic variants predisposing to non-syndromic TOF, followed by FLT4 . Together, variants in these genes are found in almost 7% of TOF patients.